2002
DOI: 10.1080/03081080290004988
|View full text |Cite
|
Sign up to set email alerts
|

On Some Properties of Convex Matrix Sets Characterized byP-Matrices and BlockP-Matrices

Abstract: In this paper, we consider convex sets of real matrices and establish criteria characterizing these sets with respect to certain matrix properties of their elements. In particular, we deal with convex sets of P-matrices, block P-matrices and M-matrices, nonsingular and full rank matrices, as well as stable and Schur stable matrices. Our results are essentially based on the notion of a block P-matrix and extend and generalize some recently published results on this topic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Real P-matrices are well known in matrix theory because they play an important role in many applications [40]. In [41], it was shown that the P-property of a single matrix is equivalent to the nonsingularity of all matrices in a certain convex matrix set.…”
Section: Real and Block P-matricesmentioning
confidence: 99%
See 2 more Smart Citations
“…Real P-matrices are well known in matrix theory because they play an important role in many applications [40]. In [41], it was shown that the P-property of a single matrix is equivalent to the nonsingularity of all matrices in a certain convex matrix set.…”
Section: Real and Block P-matricesmentioning
confidence: 99%
“…A matrix A ∈ R n×n is called a P-matrix if all its principal minors are positive [40]. On the other hand, a matrix A ∈ R n×n is a block P-matrix with respect to a partition N(λ ) of N = {1, .…”
Section: Real and Block P-matricesmentioning
confidence: 99%
See 1 more Smart Citation
“…Real P-matrices are well known in matrix theory because they play an important role in many applications (Elsner et al, 2002). In Johnson and Tsatsomeros (1995), it was shown that the P-property of a single matrix is equivalent to the nonsingularity of all matrices in a certain convex matrix set.…”
Section: Brief Introduction To Real and Block P-matricesmentioning
confidence: 99%
“…The matrix X ∈ R n×n is called a P-matrix if all its principal minors are positive (Elsner et al, 2002). On the other hand, a matrix X ∈ R n×n is a block P-matrix with respect to a partition .…”
Section: Brief Introduction To Real and Block P-matricesmentioning
confidence: 99%